2021
DOI: 10.3390/ijerph182111332
|View full text |Cite
|
Sign up to set email alerts
|

Using a Mobile Application for Health Communication to Facilitate a Sense of Coherence: Experiences of Older Persons with Cognitive Impairment

Abstract: The increasing use of technology by older persons and their preferences for living at home and being independent have created an avenue for self-care and care delivery using mobile technologies and health communication. This study aimed to explain how older persons with cognitive impairment experienced technology-based health communication through the use of a mobile application to facilitate a sense of coherence. Individual, semi-structured interviews with 16 participants in the SMART4MD project were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
3
2
0
Order By: Relevance
“…Furthermore, participants in this study indicated that the therapist-led sessions allowed for easy clarification and the ability to ask questions about the programme when required. This is again consistent with the findings from Piculell et al [ 75 ] where participants found it easier and quicker to ask for help rather than decipher the programme themselves.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, participants in this study indicated that the therapist-led sessions allowed for easy clarification and the ability to ask questions about the programme when required. This is again consistent with the findings from Piculell et al [ 75 ] where participants found it easier and quicker to ask for help rather than decipher the programme themselves.…”
Section: Discussionsupporting
confidence: 91%
“…Difficulties with using the mobile application may explain why all participants completed more sessions than scheduled. This finding is consistent with a study examining the experiences of older adults with MCI using mobile applications for health [ 75 ] which found that participants had difficulties accessing app-based content and using the different functionalities available. However, several studies have highlighted the effectiveness of computer-based interventions for improving cognition among older adults, including those with cognitive impairments [ 77 , 78 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Data analysis was conducted based on the theoretical assumptions of the SOC model for all three of its components. Although the results of the study were identified as ambiguous, SOC proved to be useful in gaining a deeper understanding of the motives for engaging in specific activities related to the use of new technologies ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…To address these challenges, several projects have been developed. For example, after a 12-week Smart Home personalized technology program, participants’ quality of life increased significantly [ 21 ], the Fik@ room web platform allowed social connection among older adults in a secure digital environment [ 22 ], and the SMART4MD mobile application [ 23 ] facilitated a sense of coherence for older persons with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%